Turmeric Sprout Inhibition and Rhizomes Quality after Post-Harvest Treatment with Gamma Irradiation - Prakhongsil, Panchalee; Sajjabut, Surasak; Pewlong, Wachiraporn; Roppon Picha; Nuatawan Thamrongsiripak (Science & Technology Asia, 2022)
A study on sprout inhibition by gamma irradiation in a fresh local variety of turmeric of was carried out. Fresh turmeric was subjected to 0 and 200 Gy and stored at ambient temperature (33.0 1.0°C), 52.5% to 66.5% RH and analyzed after 5, 30, 60 and 90 days in storage. The parameters observed were physiological weight loss, sprouting, color characteristics, total phenolic content, antioxidant activity and curcumin content. The results suggest that a dose of 200 Gy effectively inhibits sprouting in turmeric when compared to the non irradiated samples after 30 days; moreover, there was no sprouting up to 90 days of storage. The dose of 200 Gy did not affect the levels of total phenolic content, DPPH scavenging activities, ferric reducing antioxidant potentials (FRAP) or curcumin content of the turmeric rhizome. However, these values were altered with storage time. The levels of the total phenolics, DPPH, FRAP and curcumin content of both the non-irradiated and irradiated samples were 7.05 0.48 to 10.14 0.84 mg gallic acid equivalent/g, 3.43 0.29 to 4.62 0.23 mg ascorbic acid equivalent/g, 61.83 1.12 to 69.45 1.91 μmol FeSO4/ g and 5.74 0.15 to 11.20 0.85 mg/ g of samples, respectively. Therefore, gamma radiation at 200 Gy was found to be an effective post-harvest treatment for sprout inhibition and extension of shelf life of fresh turmeric rhizomes for longer than 60 days without affecting curcumin content and antioxidant activity.